2011
DOI: 10.3315/jdcr.2011.1080
|View full text |Cite
|
Sign up to set email alerts
|

Specific Pregnancy Dermatoses in 1430 females from Northern India

Abstract: Background: The specific dermatoses of pregnancy represent a heterogenous group of ill-defined pruritic skin diseases, unique to pregnancy and post partum period. Objective:The aim of our study was epidemiological and clinical evaluation of various specific dermatoses of pregnancy.Methods: All patients visiting our antenatal clinic were screened for various pruritic skin conditions and those with specific pregnancy dermatoses were identified and evaluated. Results:Out of 1430 patients screened, nearly 5% (70 c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
15
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 17 publications
3
15
0
2
Order By: Relevance
“…This finding is consistent with other authors that PUPP is seen especially in Primigravida's. 3,8 Zenon Brzoza et al found PUPP in 3 rd trimester in Primigravida's and in women with multiple gestation with incidence of 2.9 -16%. 9 Incidence of Pruritus Gravidarum was 3%.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This finding is consistent with other authors that PUPP is seen especially in Primigravida's. 3,8 Zenon Brzoza et al found PUPP in 3 rd trimester in Primigravida's and in women with multiple gestation with incidence of 2.9 -16%. 9 Incidence of Pruritus Gravidarum was 3%.…”
Section: Discussionmentioning
confidence: 99%
“…8 According to V. Shivkumar et al Prurigo of Pregnancy was the commonest specific disorder of pregnancy accounting for 9.4%. 3 Most western reports quote a low incidence of around 2%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…GÖD'lar; GPE, GİK, PG ve gebeliğin atopik erüpsiyo-nunu içeren bir grup hastalık olup, çoğunlukla ikinci ve üçüncü trimestırda ortaya çıkar 5,10 . GÖD tanılı …”
Section: Discussionunclassified
“…These were seen in 5% of 1430 patients in one study 16 . Only 1.92% of our patients were given one of these diagnoses.…”
Section: Magistral Drugs 397mentioning
confidence: 99%